2013
DOI: 10.1111/febs.12200
|View full text |Cite
|
Sign up to set email alerts
|

The ATP‐binding cassette transporter subfamily C member 2 in Bombyx mori larvae is a functional receptor for Cry toxins from Bacillus thuringiensis

Abstract: Bacillus thuringiensis is the most widely used biopesticide, and its Cry toxin genes are essential transgenes for the generation of insect‐resistant transgenic crops. Recent reports have suggested that ATP‐binding cassette transporter subfamily C2 (ABCC2) proteins are implicated in Cry intoxication, and that a single amino acid insertion results in high levels of resistance to Cry1 toxins. However, there is currently no available direct evidence of functional interactions between ABCC2 and Cry toxins. To addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
144
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(151 citation statements)
references
References 39 publications
3
144
1
3
Order By: Relevance
“…Recently, mutations of an ABCC gene (ABCC2) have been found to be linked with Bt Cry resistance in several lepidopteran insects (Gahan et al, 2010;Baxter et al, 2011;Atsumi et al, 2012;Park et al, 2014;Xiao et al, 2014), and it has been speculated that ABCC2 might play a role in facilitating the insertion of oligomeric pre-pore structure into the insect midgut membrane in the mode of action of Bt Cry toxins (Heckel, 2012). ABCC2 has recently been proved to be a functional Cry toxin receptor in B. mori (Tanaka et al, 2013), and we suspect that the role of the possibly formed white heterodimer in P. xylostella is similar to that of ABCC2 in B. mori. However, a recent study has indicated that the pre-pore oligomer does not require additional receptors in order to insert into the midgut membrane (G omez et al, 2014), suggesting that ABCC2 or white heterodimer proteins may be involved in other steps resulting in Cry toxin activity rather than being involved in the insertion of the toxin into the membrane.…”
Section: Melanogastermentioning
confidence: 99%
“…Recently, mutations of an ABCC gene (ABCC2) have been found to be linked with Bt Cry resistance in several lepidopteran insects (Gahan et al, 2010;Baxter et al, 2011;Atsumi et al, 2012;Park et al, 2014;Xiao et al, 2014), and it has been speculated that ABCC2 might play a role in facilitating the insertion of oligomeric pre-pore structure into the insect midgut membrane in the mode of action of Bt Cry toxins (Heckel, 2012). ABCC2 has recently been proved to be a functional Cry toxin receptor in B. mori (Tanaka et al, 2013), and we suspect that the role of the possibly formed white heterodimer in P. xylostella is similar to that of ABCC2 in B. mori. However, a recent study has indicated that the pre-pore oligomer does not require additional receptors in order to insert into the midgut membrane (G omez et al, 2014), suggesting that ABCC2 or white heterodimer proteins may be involved in other steps resulting in Cry toxin activity rather than being involved in the insertion of the toxin into the membrane.…”
Section: Melanogastermentioning
confidence: 99%
“…In Lepidoptera, it has been demonstrated that interaction of Cry1 toxins with aminopeptidase N (APN) and cadherin (CAD)-like) midgut proteins (2, 3) is required for toxic action, and alkaline phosphatase and ABC transporter have also been proposed as Cry1 receptors (4,5). In mosquito larvae, homologous APN, CAD-like, and alkaline phosphatase proteins have been described as Cry11 and Cry4 receptor proteins (6), and in Coleoptera a cadherin-like protein has been demonstrated to act as a Cry3Aa receptor (7).…”
mentioning
confidence: 99%
“…However, the function of most ABC transporter genes has not been analyzed without the B. mori ABC transporter subfamily C member 2 (BmABCC2), which relays transported Cry toxins from Bacillus thuringiensis (22). Aditionally, a single amino acid mutation of BmABCC2 causes a resistance to Cry toxin in B. mori (23).…”
Section: Discussionmentioning
confidence: 99%